Beyond Digital Access: A Critical Ethnography of How Teachers Navigate and Resist Neoliberal Agendas in National Online Learning Platforms - Sartinayanti, Sartinayanti; Kaso Mustamin; Muh. Safar; Andi Hidayati; Dodi Sukmayadi (PT Inovasi Pratama Internasional, 2026)
This article investigates how Indonesian school teachers navigate and resist neoliberal agendas embedded in national online learning platforms, moving the debate beyond questions of mere digital access. Drawing on a nationwide cross‐sectional survey of 482 teachers combined with critical policy analysis, the study operationalizes neoliberal logics through indicators such as marketisation of learning, datafication of performance, individualisation of responsibility, and platform‐driven managerial control. Descriptive and inferential statistics are used to map patterns of teachers’ platform use, perceived pressures, and everyday acts of compliance and resistance across school levels, regions, and employment status. The findings reveal a structurally uneven landscape in which online platforms intensify workload, extend managerial surveillance, and reconfigure professional autonomy, while simultaneously opening spaces for tactical appropriation, collegial solidarity, and critical pedagogy. Teachers in rural and under‐resourced schools report stronger experiences of platform‐mediated control but also higher engagement in collective forms of resistance. The article concludes by arguing for a re‐politicisation of digitalisation policies in Indonesian education, centring teacher agency, labour justice, and democratic accountability in the governance of national platforms